DEVELOPING ENGLISH LEARNING MATERIALS FOR GRADE TEN STUDENTS OF CULINARY ARTS STUDY PROGRAM AT VOCATIONAL HIGH SCHOOL - Deni Melyati; Tri Saswandi (EDU RESEARCH, 2024)
This study aims to develop English learning materials for Grade Ten Culinary Arts students at SMKN 3 Sungai Penuh. Using the ADDIE model, the study identified students' needs, designed materials, and evaluated their validity and practicality. The materials development process began with an analysis of students' specific requirements, followed by careful design and development to ensure alignment with vocational objectives. The resulting handouts were interactive and engaging, featuring real-world culinary scenarios, relevant vocabulary, and skill-building exercises. These materials were validated by experts and underwent limited tryouts with students and teachers, resulting in high ratings for both validity and practicality. Ultimately, the handouts demonstrated potential to enhance students' motivation, support their career readiness, and provide practical communication tools for the culinary field.